The Impact of Military Spending on Armed Conflicts in Sub-Saharan Africa - (:unkn) unknown (My University, 2025)
This research focuses on the security challenges faced by sub-Saharan African countries. Since 2000, these countries have experienced a substantial increase in military spending, mainly due to persistent and intense armed conflicts. Conflict hampers socio-economic development and risks creating vicious circles of instability, ultimately increasing the burden on public finances. The study analyses the relationship between military spending and the intensity of armed conflict. To answer the research question, we make the following basic assumption: an increase in military spending at the margin should reduce the intensity of armed conflict, given the deterrent effect of such spending. Using a dynamic probit model, we find that military spending reduces the intensity of armed conflict in sub-Saharan Africa.
Keywords: African Research